IL-17 Production from T Helper 17, Mucosal-Associated Invariant T, and γδ Cells in Tuberculosis Infection and Disease - Coulter, Felicity; Parrish, Amy; Manning, Declan; Kampmann, Beate; Mendy, Joseph; Garand, Mathieu; Lewinsohn, David M.; Riley, Eleanor M.; Sutherland, Jayne S. (Frontiers in Immunology, 2017)
IL-17 producing cells have been shown to be important in the early stages of Mycobacterium tuberculosis (Mtb) infection in animal models. However, there is very little data on the role of IL-17 in human studies of TB. We recruited TB patients and their highly exposed contacts who were further categorised based on results from an IFN-γ release assay (IGRA): 1) IGRA+ at recruitment (latently TB infected (LTBI)), 2) IGRA negative at recruitment and 6 months (non-converters (NC)) and 3) IGRA negative at recruitment and IGRA positive at 6 months (converters (C)). Whole blood was stimulated with mycobacterial antigens and analysed using Th17 multiplex cytokine assays. Th17, Vγ9Vδ2+ and CD161++Vα7.2+ Mucosal Associated Invariant T (MAIT) cells were analysed by flow cytometry. The majority of IL-17 was produced by CD26+CD4+ Th17 cells (median 71%) followed by γδ T cells (6.4%) and MAIT cells (5.8%). TB patients had a significantly lower proportion of Th17 cells and CD4+CD161+Vα7.2+ cells producing both IL-17 and IFN-γ compared to LTBI subjects. IGRA NC had significantly lower levels of CD26-CD4+ and CD8+MAIT cells producing IL-17 compared to IGRA C but had significantly higher levels of IL-17A, IL-17F, IL-21 and IL-23 in ESAT-6/CFP-10 stimulated supernatants compared to IGRA C. These data provide new insights into the role of IL-17 and IL-17 producing cells at three key stages of the Mtb infection spectrum.